Educational interests, occupational and professional expectations of bachelor’s degree in Northwest Region of Chihuahua: A gender analysis - López Salazar, Ricardo; Bautista Flores, Elizabeth; Sánchez Carlos, Óscar Arturo (IE Revista de Investigación Educativa de la REDIECH, 2019)
In this article is exposed and analyzed the results of a survey applied between 2013 and 2014, to students who attended the last year of the upper middle school level in the region known as Northwest Chihuahua (this region includes the municipalities of Ascension, Buenaventura, Janos, Galeana, Casas Grandes, Nuevo Casas Grandes, Zaragoza and Gomez Farias). The objective of this work was to know the educational interests, the labor and professional expectations according to the gender. The results obtained allowed to identify the tendencies of professional choice, the economic-social differences and even aspirational. It emphasizes that young people receive mostly the support of parents, but it is interesting the answers expressed in relation to continue with the university studies, because while the men do not assign great importance to obtain a grade, women consider a life plan that includes graduating from a bachelor’s degree and continue their graduate courses. However, labor expectations of women measured through wage income tend to be lower than men, since it does not rise to more than five thousand pesos per month. It is concluded that gender influences in a decisive way in the choice of the bachelor’s degree program, the labor and professional expectations.